Illustrated FoxPro 2.0 - Granillo, Robert (BPB book Centre , New Delhi, 1992)
Illustrated FoxPro 2.0 is a comprehensive guide to mastering FoxPro 2.0, a popular database management and programming system used in the late 1980s and early 1990s. The book focuses on teaching readers how to effectively use FoxPro 2.0 through detailed illustrations, step-by-step instructions, and practical examples. It covers various aspects of FoxPro, including database creation, data manipulation, querying, report generation, and using the FoxPro programming language for automation.
O level
Keywords: Computers; Computer science